2008
DOI: 10.1007/s00040-008-1012-7
|View full text |Cite
|
Sign up to set email alerts
|

Resolving relationships in some African fungus-growing termites (Termitidae, Macrotermitinae) using molecular phylogeny, morphology, and field parameters

Abstract: The Macrotermitinae are a large and successful subfamily of fungus-growing termites, characterised by their symbiotic association with white-rot fungi of the genus Termitomyces. The taxonomy of the subfamily, and in particular of the largest genus Odontotermes, is problematic. We used sequences of the mitochondrial 16S gene from termites occurring in East Africa and Malawi to explore the phyletic relationships within the genus Odontotermes and to place the genus in the broader context of other fungus-growing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Whenever possible specimens were identified to species level, and when this proved impossible, numbers (e.g., Microtermes sp. 1) were used to refer to unidentified species because of the complexity of Macrotermitinae taxonomy, and many species are not easy to be identified with certainty (Darlington, Benson, Cook, & Walker, ). New morphospecies were assigned numbers that followed the existing numbers in each genus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whenever possible specimens were identified to species level, and when this proved impossible, numbers (e.g., Microtermes sp. 1) were used to refer to unidentified species because of the complexity of Macrotermitinae taxonomy, and many species are not easy to be identified with certainty (Darlington, Benson, Cook, & Walker, ). New morphospecies were assigned numbers that followed the existing numbers in each genus.…”
Section: Methodsmentioning
confidence: 99%
“…Collections of soldier castes were identified to genus and sometimes to species levels using appropriate dichotomous keys (Bouillon & Mathot, 1965;Emerson, Lang, Chapin, & Bequaert, 1928;Sands, 1972Sands, , 1998, and through the reference collec- fied to species level, and when this proved impossible, numbers (e.g., Microtermes sp. 1) were used to refer to unidentified species because of the complexity of Macrotermitinae taxonomy, and many species are not easy to be identified with certainty (Darlington, Benson, Cook, & Walker, 2008). New morphospecies were assigned numbers that followed the existing numbers in each genus.…”
Section: Termite Identificationsmentioning
confidence: 99%
“…These are grass/wood feeding termites and the network of foraging galleries (4-5 mm diameter) made by this species is essentially horizontal, just a few millimetres under the crusted soil surface (Léonard and Rajot, 2001). Taxonomy of the genera Odontotermes is notoriously difficult (Darlington et al, 2008) and these species are not easy to identify with certainty (Sileshi et al, 2009). Hence, specific taxonomy of Odontotermes species in the research area during this research could not be performed.…”
Section: Introductionmentioning
confidence: 99%
“…In-depth research on the taxonomy and phylogenetics of the Odontotermes has been conducted on the African taxa. Behaviour, nest architecture, soldier morphology and molecular phylogenetics have been used to delineate some of the African species [6] , [7] , [8] . Mitochondrial DNA (mtDNA) studies have shown that some African populations are morphologically similar but have divergent 16S ribosomal RNA (16S) sequences, while others are morphologically different but have almost identical gene sequences [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%